Evaluation of Artificial Lift Methods to Increase Oil Production from Depleting Oil Wells in Gulf of Mexico - Saurabh Goswami; Dr. T. S. Chouhan (International Journal of Engineering and Management Research, 2020)
This paper summarizes the research work with reference to artificial lift methods to increase oil production form mature oil wells in Gulf of Mexico. Increase oil production or oil recovery from oil reservoirs is very important. If the average worldwide recovery factor from hydrocarbon reservoirs can be increased beyond current limits, it will alleviate a number of issues related to global energy supply. Currently the daily oil production comes from mature or maturing oil fields and reserves replacement is not keeping pace with the growing energy demand. This paper presents big picture overview of artificial lift methods for mature oil wells in Gulf of Mexico.